SISTEM INFORMASI PENGOLAHAN DATA PIUTANG PADA PT.LESTARI TOUR N’TRAVEL DENGAN MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Anastasia Veronica; Sudirman; Hasniati (KHARISMA Tech, 2020)
This study aims to design a system of receivables at PT. Lestari Tour n'Travel becomes a computerized system using Rapid Aplication Development method. Stages in the research is divided into five parts, namely, Requirements Planning, Design Workshop, Implementation. Desktop-designed apps. In the process of making this application, the author uses Visual Basic 6.0 which is part of Visual Studio 2008 for desktop-based applications.